Faktor-Faktor yang Berhubungan dengan Minat Mengikuti Imunisasi Pneumococcal Conjugate Vaccine (PCV) pada Bayi Usia 0–1 Bulan: Factors Associated with the Interest in Receiving Pneumococcal Conjugate Vaccine (PCV) Immunization among Infants Aged 0–1 Month - Soimatun, Siti; Risnawati, Risnawati; Masyita, Gita; Meihartati, Tuti; Wahyuni, Ridha (Chakra Brahmanda Lentera Institute, 2026)
Streptococcus pneumoniae infections such as pneumonia, meningitis, and bacteremia remain major causes of morbidity and mortality among children under five. The Indonesian government has implemented the Pneumococcal Conjugate Vaccine (PCV) immunization program nationally since 2022, including in Malinau Regency. However, the coverage of PCV immunization has not yet reached the established targets. The low coverage is presumed to be influenced by several factors, including maternal knowledge, family support, and access to healthcare services. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 40 mothers with infants aged 0–1 month, selected using a total sampling technique. The independent variables included maternal knowledge, family support, and access to healthcare services, while the dependent variable was the interest in participating in PCV immunization. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analysis using the Chi-Square test with a significance level of 5% (α = 0.05). The results showed that the majority of respondents had good knowledge (60.0%), good family support (67.5%), and adequate access to healthcare services (72.5%). A total of 45.0% of respondents had a high level of interest in participating in PCV immunization. Bivariate analysis indicated a significant relationship between maternal knowledge, family support, and access to healthcare services with the interest in participating in PCV immunization (p = 0.000). Maternal knowledge, family support, and access to healthcare services are significantly associated with the interest in participating in PCV immunization among infants aged 0–1 month. Continuous efforts to improve health education, strengthen family roles, and enhance access to healthcare services are necessary to increase PCV immunization coverage.